Implementation and performance analysis of wireless Ad-hoc Mesh networks - Mok, Thomas Shao Chung (2024)
Wireless ad-hoc mesh network is an effective solution to establish resilient communications, particularly in urban and rural areas prone to emergency situations. Existing approaches often rely on such network to disseminate lowbandwidth text data, which could filter the most critical information of relevance to the situation. In contrast, this project aims to develop a multi-hop Wi-Fi mesh network for high-bandwidth video streaming applications. Specifically, a testbed is built using the Better Approach to Mobile Ad-hoc Networking- Advanced (BATMAN-adv) protocol and Raspberry Pi devices. The developed mesh platform is integrated with a real-time disaster detection system, which classifies different types of natural disasters and counts the number of victims in a streaming video. A wide and rapid dissemination of these analyzed disaster information is facilitated by a proposed database synchronization system. Experimental results show that the proposed solution achieves a real-time streaming protocol (RTSP) latency of approximately 5 seconds. Besides that, the output text and image data can be synchronized within 0.59 and 0.56 second for the single-hop route. Overall, the project contributes to the development of decentralized communication platforms, offering valuable insights for future applications in disaster response systems.